1999
DOI: 10.1128/cdli.6.3.437-439.1999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Activities of Matrix Metalloproteinases 2, 8, and 9 by Chlorhexidine

Abstract: Matrix metalloproteinases (MMPs) are a host cell-derived proteolytic enzyme family which plays a major role in tissue-destructive inflammatory diseases such as periodontitis. The aim of the present study was to evaluate the inhibitory effect of chlorhexidine (CHX) on MMP-2 (gelatinase A), MMP-9 (gelatinase B), and MMP-8 (collagenase 2) activity. Heat-denatured type I collagen (gelatin) was incubated with pure human MMP-2 or -9 activated with p-aminophenylmercuric acetate (APMA), and the proteolytic degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
253
0
61

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(320 citation statements)
references
References 32 publications
6
253
0
61
Order By: Relevance
“…As the MIC of chlorhexidine, as well as of SB-3CT, is much lower than the concentration used in this study, it is probable that enzymes other than MMP-2 and MMP-9 are involved in this degradation process. For example, the role of MMP-8 might be more important than previously thought, as it is less affected by chlorhexidine (24), not affected by SB-3CT, and present in mature dentin (34). This might explain why galardine, which inhibits almost all MMPs, seems to be able to prevent degradation (6), as opposed to the SB-3CT used in our study…”
Section: Enzymatic Degradation and Mild Self-etch Adhesivesmentioning
confidence: 59%
See 2 more Smart Citations
“…As the MIC of chlorhexidine, as well as of SB-3CT, is much lower than the concentration used in this study, it is probable that enzymes other than MMP-2 and MMP-9 are involved in this degradation process. For example, the role of MMP-8 might be more important than previously thought, as it is less affected by chlorhexidine (24), not affected by SB-3CT, and present in mature dentin (34). This might explain why galardine, which inhibits almost all MMPs, seems to be able to prevent degradation (6), as opposed to the SB-3CT used in our study…”
Section: Enzymatic Degradation and Mild Self-etch Adhesivesmentioning
confidence: 59%
“…The resultant concentration in the hybrid layer is dependent on the specific technique used, but is probably always much higher than in our study, as a concentration of 0.002% prevents interface degradation for up to 6 months (26). Acid etching of dentin produces calcium salts and these are known to prevent the chelation-mediated inhibition of a low-concentrate chlorhexidine solution (24). This might interfere with the lower concentration of chlorhexidine used in this study.…”
Section: Enzymatic Degradation and Mild Self-etch Adhesivesmentioning
confidence: 60%
See 1 more Smart Citation
“…It has been demonstrated that chlorhexidine (CHX) solutions are capable of inhibiting MMPs (21) and reducing collagen fibril solubility in an aqueous medium (4), and that its application on acid-etched dentin does not negatively influence the immediate microtensile bond strength (lTBS) of adhesive systems to this substrate (22)(23)(24)(25). In addition to its recognized antimicrobial activity, encouraging results of recent in vivo (22,26,27) and in vitro (22,23,25,28,29) studies have demonstrated that the application of CHX to dentin between acid etching and adhesive system application seems to prevent, or at least decelerate, the degradation of collagen fibrils exposed at the bottom of the hybrid layer.…”
mentioning
confidence: 99%
“…To remove smear layer, 17% EDTA solution was used, which isas the 2% chlorhexidine solutionthe concentration usually found in the endodontic literature (Zamany et al 2003, Zehnder 2006. As a final irrigation, chlorhexidine has various advantages, such as its substantivity (Rolla et al 1971, Carrilho et al 2010) and its broad antimicrobial activity (Ruff et al 2006, Arias-Moliz et al 2009, Rasimick et al 2010) and, especially when using methacrylate-based sealers, its broad-spectrum matrix metalloproteinase (MMP)-inhibiting effect (Gendron et al 1999), which can significantly improve resin-dentine bond stability (Hebling et al 2005, Mohammadi & Abbott 2009, Carrilho et al 2010. Another reason for using chlorhexidine as the final irrigant instead of NaOCl is that sodium hypochlorite has a negative effect on the shear bond strength of resin-based sealers to dentine (Nassar et al 2011).…”
Section: Discussionmentioning
confidence: 99%